2020
DOI: 10.21203/rs.3.rs-88923/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lower Starting Dose of Afatinib for the Treatment of Metastatic Lung Adenocarcinoma Harboring Exon 21 and Exon 19 Mutations

Abstract: BackgroundAfatinib has shown favorable response rates (RRs) and longer progression free survival (PFS) in lung cancer patients harboring EGFR mutations compared with standard platinum-based chemotherapy. However, serious adverse drug reactions (ADRs) limit the clinical application of afatinib. MethodsWe designed a retrospective study, enrolled all patients with metastatic lung adenocarcinoma who were diagnosed and treated with 30 or 40 mg afatinib as their starting dose in three Kaohsiung Medical University-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(55 reference statements)
0
2
0
Order By: Relevance
“…In fact, more severe AEs were observed in patients who received the standard 40 mg afatinib daily compared with those who received a first-generation EGFR-TKI, such as gefitinib or erlotinib. 31 Therefore, in clinical practice, many clinicians prescribe a lower starting dose of afatinib 32,33 or perform dose modifications 34,35 to improve patient outcomes and adherence, 31 without compromising its beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, more severe AEs were observed in patients who received the standard 40 mg afatinib daily compared with those who received a first-generation EGFR-TKI, such as gefitinib or erlotinib. 31 Therefore, in clinical practice, many clinicians prescribe a lower starting dose of afatinib 32,33 or perform dose modifications 34,35 to improve patient outcomes and adherence, 31 without compromising its beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent clinical trial that enrolled patients with metastatic lung adenocarcinoma who were treated with either 30 mg or 40 mg afatinib daily as first-line treatment demonstrated that patients who received an initial afatinib dose of 40 mg daily required dose reduction (or discontinuation) more frequently than those who initially received 30 mg daily (40% vs. 8%); however, this study did not discriminate between patients with Ex19Dels and those with exon 21 L858R point mutations. 31…”
Section: Discussionmentioning
confidence: 99%